Indeks Kesehatan Mangrove Dan Potensi Karbon Vegetasi Mangrove Pada Kawasan Wisata Bahari Nusantara Dian Center, Kelurahan Molas, Kecamatan Bunaken, Provinsi Sulawesi Utara - Joshian Nicolas William Schaduw (SPATIAL: Wahana Komunikasi dan Informasi Geografi, 2021)
The research aims at determining the health condition of mangroves in the Nusantara Dian Center (NDC) in Molas Village, Bunaken District, Manado City, North Sulawesi Province. The research method used the line transect plot method to collect community structure data and the hemisperichal photography method to collect canopy cover percentage data. The obtained data were entirely inputted and analyzed using the MonMang application to determine the mangrove healthy index (MHI). The analysis results showed that average health condition of the mangroves at each station was in the moderate category, and the condition of the mangrove canopy cover remained in the good category with the density value of medium and rare category based on the Minister of Environment Decree Number 201 of 2004 concerning the criteria for mangrove damage. For the potential carbon storage of mangrove vegetation, total average value reaches 32.91 tons C/ha or 120.80 tons CO2/ha.